Cosine bend-linear waveguide digital optical switch with parabolic heater - Yulianti, Ian (Elsevier Limited, 2010)
A new digital optical switch (DOS) with large branching angle and short device length that exhibits low crosstalk and low power consumption is demonstrated. The Y-branch shape was optimized by introducing constant effective refractive index difference between branches (?Neff) along the propagation direction through beam propagation method (BPM) scheme. To provide decreasing local branching angle that results in the improvement of the crosstalk, two modified cosine bend was introduced to form the Y-branch. The modified cosine branch was then connected to a linear branch. The heater electrode was optimized so that the temperature fields induce a constant ?Neff to satisfy initial assumption in designing the Y-branch shape. With branching angle of 0.299° and device length of only 5 mm, the simulation shows that the device could exhibits crosstalk of -33 dB at calculated required power of only 26 mW.